The roles of comovement and inventory investment in the reduction of output volatility - F. Owen Irvine; Scott Schuh (Federal Reserve Bank of Boston, 2005)
Most of the reduction in GDP volatility since the 1983 is accounted for by a decline in comovement of output among industries that hold inventories. This decline is not simply a passive byproduct of reduced volatility in common factors or shocks. Instead, structural changes occurred in the long-run and dynamic relationships among industries' sales and inventory investment behavior-especially in the automobile and related industries, which are linked by supply and distribution chains featuring new production and inventory management techniques. Using a HAVAR model (Fratantoni and Schuh 2003) with only two sectors, manufacturing and trade, we discover structural changes that reduced comovement of sales and inventory investment both within and between industries. As a result, the response of aggregate output to all types of shocks is dampened. Structural changes accounted for more than 80 percent of the reduction in output volatility, thus weakening the case for good luck, and altered industries' responses to federal funds rate shocks, thus suggesting the case for better monetary policy is complicated by changes in the real side of the economy.
Keywords: E22; E32; E52; L16; 330; Inventory investment; GDP volatility; comovement; business cycles; HAVAR